Commentary: Old Self vs. New Self. (16th September 2016) - Beasley, Kara D.
Abstract : Implantation of deep brain stimulator (DBS) leads for Gilles de Tourette syndrome was first described by Visser-Vanderwalle et al., with a reported 70%–90% decrease in tic frequency. 1 Since that time, several targets, including the basal/ganglia and striatum, have been described. The target remains experimental, and in this case, leads were implanted under an investigator-initiated research protocol. Ms. L. reported an excellent intraoperative reduction in the "urge to tic" that persisted for 15 weeks postoperatively, indicating that the leads were well placed. Furthermore, although her tic frequency has increased, it remains improved from baseline and returns to baseline when stimulation is discontinued. Although her response does not represent what her treatment team would consider the "desired medical/therapeutic outcomes, " there is no question that the patient recognizes benefit from her stimulation. In fact, she clearly states that "it's like I've felt a new way and don't want to go back to the old way."